Nutrition- Taste- Lifestyle - Lâm Thị Ánh Quyên (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Khoa học Xã hội, 2013)
Nutrition and eating belongs to one of the most basic physiological needs of human beings. But what people eat or do not eat, how the food is prepared,... are regulated by society and varies widely from culture to culture and social classes. Each person when facing the decision to choose food to consume is affected by many different factors. This article focuses on nutrition and eating in the sociological perspective and the influence of taste on the nutritional habits of different social classes.